2014
DOI: 10.1007/s00540-014-1865-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of thoracic epidural analgesia with risk of atrial arrhythmias after pulmonary resection: a retrospective cohort study

Abstract: Purpose Atrial arrhythmias are common after non-cardiac thoracic surgery. We tested the hypothesis that TEA reduces the risk of new-onset atrial arrhythmias after pulmonary resection. Methods We evaluated patients who had pulmonary resection. New-onset atrial arrhythmias detected before hospital discharge was our primary outcome. Secondary outcomes included other cardiovascular complications, pulmonary complications, time-weighted average pain score over 72 h, and duration of hospitalization. Patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Direct sympathetic nerve block by epidural analgesia is thought to be the reason why it reduces postoperative tachyarrhythmias in cardiac surgery . However, the anti‐arrhythmic effect of epidural analgesia is debatable in thoracic surgery . Blockade at the level of T1–T4 is required for cardiac sympathetic fibres.…”
Section: Discussionmentioning
confidence: 99%
“…Direct sympathetic nerve block by epidural analgesia is thought to be the reason why it reduces postoperative tachyarrhythmias in cardiac surgery . However, the anti‐arrhythmic effect of epidural analgesia is debatable in thoracic surgery . Blockade at the level of T1–T4 is required for cardiac sympathetic fibres.…”
Section: Discussionmentioning
confidence: 99%
“…The pain score reported was at the body locations relevant for postcesarean delivery (i.e., incisional pain, abdominal pain, and pelvic pain). TWA pain score was equal to the sum of the portion of each time interval in between two adjacent pain score measurements multiplied by the average of the corresponding two pain scores that was then divided by the time interval between the first and the last pain score measurements [ 13 , 14 ]. Therefore, it could be calculated even if the pain scores were not reported every 4 hours or the pain scores were not reported for certain periods of time [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…TWA pain score was equal to the sum of the portion of each time interval in between two adjacent pain score measurements multiplied by the average of the corresponding two pain scores that was then divided by the time interval between the first and the last pain score measurements [ 13 , 14 ]. Therefore, it could be calculated even if the pain scores were not reported every 4 hours or the pain scores were not reported for certain periods of time [ 14 ]. TWA pain score was calculated from all the available pain scores during the postoperative 48-hour study period.…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted by Komatsu et al, it was observed that the use of epidural analgesia did not yield a statistically significant reduction in the incidence of POAF compared to general anesthesia during pulmonary resection. However, patients receiving epidural analgesia tended to experience fewer postoperative cardiovascular complications ( 95 ). Similarly, in patients undergoing major abdominal surgery with a history of myocardial injury, thoracic segment epidural analgesia was found to reduce the occurrence of arrhythmias, including AF ( 96 ).…”
Section: Introductionmentioning
confidence: 99%